Digital Government Implementation and its Implications for Accounting Systems and Data Security - Noordiyati, Noordiyati; Fakhri, Fakhri (Advances in Applied Accounting Research, 2025)
Purpose: This study investigates the implications of digital government implementation on public sector accounting systems and data security. The purpose is to explore how digital technologies enhance financial management transparency and accountability while addressing the challenges related to data security in public administration. Research Design and Methodology: The research adopts a qualitative approach using a systematic literature review (SLR) to analyze relevant studies on digital government, accounting systems, and data security. The methodology involved reviewing recent articles and studies to understand the subject comprehensively. Findings and Discussion: The findings reveal that technologies such as cloud computing, AI, machine learning, and blockchain have significantly improved the efficiency and accuracy of public sector financial reporting. Blockchain enhances transparency by ensuring the immutability of financial transactions. However, the study also highlights challenges such as cybersecurity risks, data breaches, and the need for comprehensive data governance frameworks. The findings emphasize the importance of human resources preparedness and infrastructure readiness to implement digital accounting systems effectively. Implications: The study’s practical implications suggest that policymakers must invest in secure digital infrastructure, provide continuous training for government employees, and establish strong data governance frameworks. These strategies are critical for ensuring digital government systems' effectiveness, security, and accountability.